Determination of cyclosporine and everolimus blood levels compared between the cobas e411 and Indiko Plus automated chemistry analyzers - Keawvijit, Tippanate; Pakdeenukoolkijja, Supawadee; Boonprasert, Rasda; Kolladarungkri, Teera (Archives of Allied Health Sciences, 2019)
To compare the efficacy of electrochemiluminescence immunoassay (ECLIA) to measure cyclosporin (CsA) and everolimus (EVL) blood levels on the cobas e411 automated chemistry analyzer (Roche Diagnostics) versus the efficacy of cloned enzyme donor immunoassay (CEDIA) to measure CsA blood level and the Quantitative Microsphere System (QMS) to measure EVL blood level on the Indiko Plus automated chemistry analyzer (Thermo Fisher Scientific). This comparative study included 40 blood samples that were collected for measurement of CsA and 40 blood samples that were collected for measurement of EVL that were analyzed at the Clinical Toxicology Laboratory of the Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand. CsA and EVL blood level results were statistically analyzed and compared between the two automated analyzer. The precision of internal quality control for CsA and EVL measurement using the automated cobas e411 analyzer ranged from 1.51 to 5.05 %CV. The Pearson’s correlation coefficient (r > 0.95, p-value <0.01) indicates a strong positive correlation. The results of linear regression revealed good correlation between the two compared systems (r2 ≥ 0.90). The percentages of bias ranged from 2.11% to 2.69% for CsA, and from 12.29% to 12.61% for EVL. Statistically significant differences were observed between group means, as determined by ANOVA (p<0.01). Calculated total errors were within acceptable range for all evaluated parameters. The results of this study revealed that ECLIA on the cobas e411 system demonstrated good analytical performance that correlated well with the results of the CEDIA and QMS assays on the Indiko Plus system. Accordingly, the cobas e411 system should be introduced into routine practice for determination of CsA and EVL blood levels.